التقريب بين المسيحية والإسلام : من وجهة نظر الشيخ محمد الغزالي رحمه الله - Qasim Haji Ramli (Kuliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 1998)
The idea of religious reapproachment (taqrib) specifically between Christianity and Islam has become the most significant issue in the present century, especially during the last decades. It calls for establishing a dialogue between the adherents of the two religions with the hope to create a peaceful co-existence in accordance with basic values of mercy, the dignity of mankind, and unity among human races. This study analyses the meaning of taqrib, its historical root, its objective, its common shared grounds and its conditions to achieve this global project based on the teachings of Christianity and Islam. It deals with analytical and historical methodology of taqrib amongst the former and contemporary Muslim thinkers, and examines special statements issued by the Second Vatican Council, Christian theologians and thinkers to the significant issue. It concludes that the need to build up this global project must be based on the common shared grounds such as belief in the Oneness of Allah, and other doctrines which are strongly related to the meaning of social justice, peaceful co-existence, common good and prohibited evil, and mutual respect for each others' beliefs. The Late Syeikh Muhammad al-Ghaz.ali provides an example in explaining Islamic views and their profound dimensions rooted in this global project.